Achieving job satisfaction - Kepler, Kay ed. (Crisp Pub. Menlo ParkUS, 1994)
Explores in depth the 10 sources of job satisfaction namely: productivity, quality of work, learning, expressing creativity, professionalism, recognition, teamwork, social satisfaction, personal growth, and work environment. 10 attitude traps are aslo examined and suggestions are provided for escaping them. Attitude traps identified include: underemployment, failing to balance home and career, and conflict with the boss.